Protein losing enteropathy in two children with epidermolysis bullosa junctional type and congenital pyloric atresia. - Mahadevan, SBK; Morrice, JS; Gould, S; Sullivan, PB (European Journal of Pediatric Dermatology, 2006)
We report two brothers with junctional epidermolysis bullosa and congenital pyloric atresia with protein-losing enteropathy. The first sibling presented at 3 years of age following a viral gastroenteritis and the younger at 3 months. Both were edematous with hypoalbuminemia, hypokalemia and elevated fecal alpha-1 antitrypsin. The clinical course of the illness was determined by the protein-losing enteropathy with both developing chronic diarrhea with moderate to severe dehydration, failure to thrive and septicemia and requiring total parenteral nutrition and antibiotic therapy. In both cases histological evidence was obtained which showed the loss of surface epithelium of the small intestine. Glucocorticoids appeared to lead to a clinical improvement in the elder sibling who is now 5 years old and is alive and well. His brother died at 8 months of age.